(untitled) (Scientific journal of the Fergana State University, 2023)
The article examines on example of the tale “Kezargon Boychechak” by Anvar Obidjon the formation of the ideas of national self-consciousness, the feeling of love for the Motherland. It features the writer’s ability to use the traditions of folklore.